Problem Pemberian Amnesti oleh Presiden Dalam Perspektif Kepentingan Negara - Rizky Malinto Ramadani; Indra Perwira; Bilal Dewansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Article 14 Paragraph (2) of the 1945 Constitution determines that the President grants amnesty and abolition by taking into account the considerations of the House of Representatives. in the provisions of Article (1) of the Emergency Law no. 11 of 1954 concerning Amnesty and Abolition states that "The President, in the interest of the state, can grant amnesty and abolition to people who have committed a criminal act. The President granted this amnesty and abolition after obtaining written advice from the Supreme Court which conveyed the advice at the request of the Minister of Justice.” The issue related to amnesty is that there is no more detailed clarity regarding the criteria for granting amnesty for the benefit of this country, whether the granting of amnesty is only intended for politically charged cases or can also be given for general criminal acts, especially in history, amnesties have been granted only for political crimes. The identification of the problems in this study are: First, the extent to which the granting of amnesty in Indonesia is in accordance with the criteria of the state's interest. The method used by researchers in this study is normative juridical. The results of this study indicate that the most important criterion of the existence of the state's interest is the stability of the state administration system and the guarantee of rights for citizens. The ideal conditions that need to be regulated in amnesty are: Amnesty restrictions are not granted for extraordinary crimes; not allowed to impeach the President. As for the ideal procedure, apart from referring to the 1945 Constitution and the Regulation of the Minister of State Secretary, the granting of amnesty must also ask for consideration from the Supreme Court, so that the granting of amnesty is not only seen for political interests, but also for the interests of the state.